Business Sustainability Based on Digital Marketing, Entrepreneurial Passion, and Self-Efficacy in MSMEs as Cooperative Members - Awa Awa; Afzil Ramadian; Yoyok Priyo Hutomo; Saepul Alam; M. Albi Sahal Ma’hadi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Many micro, small, and medium enterprises (MSMEs) remain conventional, hindering their business sustainability. A key strategy to achieve sustainability is digital marketing, which helps MSMEs adapt to digital transformation. Alongside this, entrepreneurial passion and self-efficacy are essential in improving competitiveness and performance. However, studies that examine the combined influence of digital marketing, entrepreneurial passion, and self-efficacy on MSMEs' sustainability—especially among cooperative members—are still limited. This study analyzes their influence on MSMEs in Cisarua and Cijeruk districts, Bogor Regency, using a quantitative approach with census sampling of 62 cooperative-member MSMEs. Data were analyzed using multiple linear regression with SPSS 19. The results show that digital marketing, entrepreneurial passion, and self-efficacy each significantly influence business sustainability, both partially and simultaneously. These findings offer insights for researchers, policymakers, and MSME actors, and encourage further studies across various sectors.